The Function of the NMDA Receptor in Hypoxic-Ischemic Encephalopathy - Zhang, Xiaotong; Peng, Kaizhen; Zhang, Xiaomin (Frontiers in Neuroscience, 2020)
Hypoxic-ischemic encephalopathy (HIE) is one of the main forms of neonatal brain injury. Not only does it cause neonatal death, but it also leads to neonatal disability. Therefore, HIE strongly affects the health of newborns, and furthermore, it brings heavy burden to the family and society. It is well studied that N-methyl-d-aspartate (NMDA) receptors are involved in excitotoxicity induced by hypoxia ischemia in adult brain. And recently, it has been shown that the NMDA receptor also plays important roles in HIE. In this review, we made a summary of the molecular mechanism of NMDA receptor in the pathological process of HIE, focusing on the distinct role of GluN2A- and GluN2B-containing NMDA receptor subtypes, aiming to provide some insights into the clinical treatment and drug development of HIE.